Perlecan/HSPG2: Signaling role of domain IV in chondrocyte clustering with implications for Schwartz‐Jampel Syndrome. Issue 2 (11th September 2018) - Martinez, Jerahme R.; Grindel, Brian J.; Hubka, Kelsea M.; Dodge, George R.; Farach‐Carson, Mary C.
Abstract: Perlecan/heparan sulfate proteoglycan 2 (HSPG2), a large HSPG, is indispensable for the development of musculoskeletal tissues, where it is deposited within the pericellular matrix (PCM) surrounding chondrocytes and disappears nearly completely at the chondro‐osseous junction (COJ) of developing long bones. Destruction of perlecan at the COJ converts an avascular cartilage compartment into one that permits blood vessel infiltration and osteogenesis. Mutations in perlecan are associated with chondrodysplasia with widespread musculoskeletal and joint defects. This study elucidated novel signaling roles of perlecan core protein in endochondral bone formation and chondrocyte behavior. Perlecan subdomains were tested for chondrogenic properties in ATDC5 cells, a model for early chondrogenesis. A region within domain IV of perlecan (HSPG2 IV‐3) was found to promote rapid prechondrocyte clustering. Introduction of the mutation (R3452Q) associated with the human skeletal disorder Schwartz‐Jampel syndrome limited HSPG2 IV‐3‐induced clustering. HSPG2 IV‐3 activity was enhanced when thermally unfolded, likely because of increased exposure of the active motif(s). HSPG2 IV‐3‐induced clustering was accompanied by the deactivation of key components of the focal adhesion complex, FAK and Src, with increased messenger RNA (mRNA) levels of precartilage condensation markers Sox9 and N‐cadherin ( Cdh2 ), and cartilage PCM components collagen II ( Col2a1 ) and aggrecan ( Acan ). HSPG2 IV‐3 reduced signaling through the ERK pathway, where loss of ERK1/2 phosphorylation coincided with reduced FoxM1 protein levels and increased mRNA levels cyclin‐dependent kinase inhibitor 1C (Cdkn1c) and activating transcription factor 3 ( Atf3 ), reducing cell proliferation. These findings point to a critical role for perlecan domain IV in cartilage development through triggering chondrocyte condensation. Abstract : This study identified a novel active chondrogenic region within domain IV of the perlecan core protein with direct relevance to cartilage development and dysplasia. We showed that HSPG2 IV‐3 induced cell‐cell interactions reminiscent of mesenchyme stem cell condensation and elevated major markers associated with chondrocyte differentiation. Introduction of a mutation associated with Schwartz‐Jampel syndrome abrogated the clustering activity of HSPG2 IV‐3, which may partially explain the cartilage dysmorphisms seen in patients with this mutation. Together, these results point to a key role for the perlecan core protein in chondrocyte condensation in the developing growth plate cartilage, which is disrupted in certain chondrodysplasias.